Food and Beverage Services: Communication Management in Handling Guest Complaints at Three-Star Hotels in Bogor - Budayasa, I Ketut; Hengky, SH (Publikasi Inspirasi Indonesia, 2025)
This observe explores the function of conversation control in handling guest complaints in the food and Beverage (F&B) departments of three-Star resorts in Bogor. powerful verbal exchange is important in addressing guest worries directly and professionally, making sure carrier recuperation, and retaining basic visitor pleasure. using a quantitative studies design, records had been amassed from 100 respondents, consisting of hotel visitors and F&B body of workers, via based questionnaires. The statistics were analyzed the usage of SPSS 26.0, incorporating descriptive information, validity and reliability assessments, and one-manner ANOVA to take a look at variations in perceptions of conversation effectiveness. The effects suggest that empathy and readability are the most influential dimensions of communication in positively impacting guest pride, while responsiveness changed into recognized as an area requiring improvement. those findings emphasize the importance of dependent criticism-dealing with protocols, centered communication education for F&B personnel, and systematic monitoring to decorate service restoration. The observe presents practical suggestions for lodge managers aiming to improve operational efficiency and enhance purchaser relations thru powerful communique control.